The Experience and Inspiration of Japanese Vocational Schools: The Example of Kobe Institute of Computing - Yiwei Sha (Journal of Advanced Research in Education, 2023)
The history of vocational schools in Japan is short, but they have developed rapidly and have provided a large number of professional talents for the development of Japanese economy. Kobe Institute of Computing has remained strong despite the declining birth rate and unstable economic conditions in Japan. The author analyzes and discusses the basic situation and characteristics of its profession, curriculum, and educational philosophy, which is of great practical significance and reference for the development of higher vocational education in China.